The Effect of Using Edmodo Application on The Student’s Critical Reading - Alda; Sulfasyah; Zia UI Haq, Muhammad (Journal of Computer Interaction in Education, 2019)
The research aims to know the effect of using Edmodo for online learning on students’ critical reading, focusing on narrative text, especially characteristics, theme, and moral message. The writer applied the experimental method with one group pretest-posttest design and collected the data based on the test. The population used is English Department students at the Muhammadiyah University of Makassar, totaling 90 people. The research sample was from the fourth semester of Unismuh, consisting of 23 students with a purposive sampling technique. A Data analysis technique was used, descriptive statistics and t-test, and the processing results showed that the data were normally distributed. The research findings showed that the 4th-semester students of Muhammadiyah University Makassar had poor scores in a pre-test. After treatment, their reading ability in the narrative text increases significantly. The result of the research was that the mean score of reading narrative text in terms of identifying characteristics obtained by the students through the pre-test was 76, and the post-test was 87. The mean score for reading narrative text identifying themes obtained by the students through the pre-test was 75, and the post-test was 86. The mean score for reading narrative text identifying moral messages received by the students through the pre-test was 74, and the post-test was 86. Reading narrative text in terms of identifying characteristics improved by 16.2%, theme improved by 15%, and moral message improved by 14.4%. Hypothesis testing could be done using a t-test. So, the calculated value pre-test was 75.34 and, the post-test was 82.94, P was 0,001> 0,05; thus, it can be concluded that there was a significant effect of using Edmodo in improving students’ critical reading.